The Effect of Knowledge Management and Organizational Culture on Employee Performance at PT SBC Berkah Bersama - Khumairoh, Dini Nur; Adiwaty, Mei Retno (Journal of Applied Business, Taxation and Economics Research, 2025)
The retail industry has rapidly developed in recent years. This shift is caused by increasingly intense competition, and in order to compete with rivals and maintain their position, retail companies must have the ability to adapt to changing times. This research aims to explore the implications of knowledge management and organizational culture on the performance of employees at PT SBC Berkah Bersama. Using a quantitative method with Partial Least Square data analysis technique. The sampling technique used the probability sampling method with simple random sampling technique involving 95 employees as respondents. The findings of the research show that knowledge management has a positive effect on employee performance and organizational culture has a positive effect on employee performance. This research shows that knowledge management and organizational culture are crucial factors to improve employee performance. This research also contributes to the understanding of how knowledge management and organizational culture influence employee performance especially for retail companies.